Variational Approximation in Modular Spaces by Using Finite Element Method Approach. (2nd January 2023) - Mabdaoui, Mohamed; Moussa, Hicham; Rhoudaf, Mohamed
Abstract: In this paper, we shall study the polynomial approximation in a more general setting namely to consider the Orlicz-Sobolev spaces W k L M ( Ω ) . We study the local and global interpolation estimate and we will show the finite element error estimate for a nonlinear elliptic problem where we establish a generalization of Cea's Theorem and we prove the modular convergence of the gradient, then we present the existence result and its proof.